Persepsi Masyarakat terhadap Alun-alun Kalirejo sebagai Ruang Publik Kota Ungaran - Dyah Candrarini; Hadi Wahyono (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Urban areas are regions with non-agricultural activities. The composition of urban areas functions as settlement, centralization and distribution of government services, social services, and economic activities. One of the urban social service facilities is public space. Square is one form of the public space that the service covers entire city. In Indonesia, the existence of the square is believed to serve as a center of public activity that eventually leads as an icon of a city. In 2014, the Government of Ungaran City inaugurated a square namely Kalirejo Square. Ungaran City has previously had two square that so cramped to do activities in it. So it does not take long, Kalirejo Square instantly has its own charm, considering this is a new thing for the citizens of Ungaran City. Its strategic location, which is straight on the exit of Ungaran Highway, create wide range of services area. Ocasionally encountered visitors from outside the city of Ungaran. The spacious field is also able to provide various facilities to meet the needs of visitors, such as playgrounds, street vendors, parking lots, meeting hall, green fields, toilets, prayer room (musala), up to the arena of tour vehicles and skates. Based on this background, the research question arises that is "how the public perception of Kalirejo Square as public space of Ungaran City". In accordance with the research questions, the purpose of this study is to examine the actual condition of Kalirejo Square and to examine the public perception after three years of the inauguration of Kalirejo Square as a new icon of this Ungaran City. The result conducted in this research is to study of the physical condition of Kalirejo Square, the research of public perception of Kalirejo Square as a public space of Ungaran City. According to the research conducted, Kalirejo square meets the criteria of good public space on the aspect of image and identity, accessibility, amenities, and attraction and destination, but Kalirejo Square does not meet the criteria of flexible design. In addition, many facilities in Kalirejo Square are in need of repair, but can’t be done yet because at the beginning of 2017, manager of the Government of Semarang Regency, formerly DPPKAD and Disperindag become Tourism Department.